Keanekaragaman parasitoid dan predator kutu lak (Laccifer lacca Kerr) di KPH Probolinggo Perum Perhutani Unit II, Jawa Timur - Suheri, Mohamad; Haneda, Noor Farikhah (Jurnal Entomologi Indonesia, 2019)
Lac insect (Laccifer lacca Kerr) (Homoptera: Kerriidae) is an insect species that attack various plant species and produce lac as a by-product. The insects produce compact and thick natural resin and attached to the branch commonly called shellac. Branch lac is a natural resin from the secretion process of insects named L. lacca in the form of a thick-layered lac that covering the branches of the host plant. Parasitoids and predators attack lac insect has a direct impact on the decrease in shellac productivity. The aim of the research is to determine the dynamics of parasitoid populations on lac insect, the diversity of parasitoids and predators attacking lac insect, identification parasitoids and predators that attack to lac insect, measuring parasitization level in BKPH Kabuaran and Taman, KPH Probolinggo, Perum Perhutani Unit II - East Java. Samples branch lac of BKPH Kabuaran and Taman each of 200 lac branch was collected. The dominant families of parasitoids found are Aphelinidae, Encyrtidae, and Eulophidae. Predators found to consist of Family Lathridiidae (Coleoptera), Cosmopterigidae and Noctuidae (Lepidoptera), Nabidae (Hemiptera), and Chrysopidae (Neuroptera). The cumulative amount of parasitoids in the field is more high (5.900 individuals) than in warehouses (5.263 individuals). The highest increase of individual parasitoids in the field and warehouses occurred at the observation day 7th to 17th. The parasitization level of lac insect in the field and warehouse was high i.e., 93% and 96% respectively. It can be concluded that lac insect from both the field and werehouse are alike parasitized.